Fabrication of Medium Density Fibre Board From Oil Palm Frond Using Waste Low Density Polyethylene (LDPE) Composites as Possible Partial Replacement For Binder - Fakhri Fadullilah, Sulaiman (2013)
There are two objectives in this research. The first objective is to produce the high quality of medium density fibre board from waste biomass material, oil palm frond mixed with waste LDPE composites at the same time reducing the percentages of urea formaldehyde resin. The second objective is to characterize the physical and mechanical properties of fibre board. This research is very important to environment, it is one of the solution in order to reduce the emmission of toxic formaldehyde from MDF. Different composition are use in order to produce the high fibre board in terms of strength and swelling effect. In industry, urea formaldehyde is use as a binder in fibre board manufacturing. In this research, the waste LDPE composite is selected as a possible partial replacement for binder in order to reduce the emission of toxic formaldehyde. Based on this research, the high quality fibre board can be produced which achieved the industrial requirement but strictly limited in its application.